Analisis Pengaruh Anggaran Biaya Produksi dan Anggaran Kas Terhadap Anggaran Perencanaan dan Pengendalian Perusahaan Dagang: Literature Review Akuntansi Manajemen - Depita Anggraini; Rizqy Aiddha Yuniawati; Ni Kadek Ayu Nirwana; Sugianto Sugianto; Sarni Handayani Puspita Sari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
A budget is a management tool that serves as currency for day-to-day operations and ensures that organizational goals are met. The purpose of this study is to analyze the effect of the production cost budget and cash costs on the planning and control budget of trading companies. The method used in this article is a qualitative method with a literature study or Library Research. The aim is to analyze the comparison of existing theories with previous theories in the research literature. Based on the results and discussion in this article, it can be concluded as follows: (1) The production cost budget affects the Planning and Control Budget of Trading Companies. (2) The cash budget affects the Planning and Control Budget of the Trading Company. Keywords: production cost budget, cash budget, planning and control budget